Effect Complete Feed Containing Starch Tubers of Different Varieties of Banana Plants on pH, NH3 and VFA of Kacang Goat - . Aswandi; C. I. Sutrisno; M. Arifin; A. Joelal (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
The purpose of this study was to examine digestibility of complete feed containing starch tubers from different varieties of banana plants. The experiment was run according to completely randomized design with six treatments of complete feed rations containing starch tubers of different banana varieties (control/without tubers and five different banana starch tubers: ambon, kepok, batu, susu, and raja) and three replication for each treatment. The results showed that treatment of complete feed did not significantly affect (P>0.05) ruminal NH3 produced. However the treatment of complete feed significantly affected (P<0.05) rumen fluid pH. Furthermore, production of individual volatile fatty acids/VFA (asetat, propionat, and butirat) was significantly (P<0.05) different among the treatments. The highest production of volatile fatty acids (VFA) was obtained from the complete feed containing banana starch tubers of batu.